Conductive paste, electronic component, and laminate ceramic capacitor
The conductive paste composition with controlled viscosity and filtration addresses the issue of coarse particle removal in multilayer ceramic capacitors, ensuring excellent dispersibility and smooth electrode layers for high-performance capacitors.
Patent Information
- Application Number
- JP2023110357
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
AI Technical Summary
Existing methods for producing conductive pastes for multilayer ceramic capacitors struggle to effectively remove coarse particles, leading to reduced yield and poor dispersibility, especially in highly viscous pastes, due to re-agglomeration and clogging issues during filtration.
A conductive paste composition comprising inorganic particles, a binder resin, and a dispersant, with controlled viscosity and filtration accuracy, significantly reduces coarse particles by using a specific dispersant and filtration method, ensuring excellent dispersibility and high viscosity.
The conductive paste achieves a substantial reduction in coarse particles, maintaining high viscosity and dispersibility, enabling the formation of thin, smooth internal electrode layers in multilayer ceramic capacitors with improved reliability and productivity.
Smart Images

Figure 2025008309000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive paste, an electronic component, and a multilayer ceramic capacitor. [Background technology]
[0002] As electronic devices such as mobile phones and digital devices become smaller and more powerful, there is a demand for smaller electronic components, including multilayer ceramic capacitors, with higher capacitance. Multilayer ceramic capacitors have a structure in which multiple dielectric layers and multiple internal electrode layers are alternately stacked, and by thinning these dielectric layers and internal electrode layers, it is possible to achieve smaller size and higher capacitance.
[0003] For example, a multilayer ceramic capacitor is manufactured as follows. First, a conductive paste for internal electrodes is printed in a predetermined electrode pattern on the surface of a green sheet containing a dielectric powder such as barium titanate (BaTiO3) and a binder resin, and then dried to form a dry film (conductive film). Next, the dry film and the green sheet are alternately laminated to obtain a laminate. Next, this laminate is integrated by heat and pressure bonding to form a pressure-bonded body. This pressure-bonded body is cut, and an organic binder removal process is performed in an oxidizing atmosphere or an inert atmosphere, and then sintered to obtain a sintered chip. Next, a paste for external electrodes is applied to both ends of the sintered chip, and after sintering, nickel plating or the like is performed on the surface of the external electrodes to obtain a multilayer ceramic capacitor.
[0004] As multilayer ceramic capacitors become smaller and have larger capacitance, the thickness of both the internal electrodes and dielectrics is being reduced. Accordingly, the particle size of the conductive powder (e.g., nickel powder) used in the conductive paste for the internal electrodes is also becoming finer, and nickel powder with an average particle size of 0.4 μm or less may be required. Although it depends on the thickness of the internal electrodes, the standard particle size is usually set to about 3 to 5 times the number average particle size of the entire conductive powder, and particles larger than this standard particle size are considered to be coarse particles. Furthermore, as multilayer ceramic capacitors become smaller and the internal electrode layers become thinner in recent years, a standard particle size smaller than the number average particle size of the conductive powder may be required.
[0005] Here, when the conductive powder is mainly composed of primary particles, the coarse particles include not only large particles whose primary particle diameter is equal to or larger than the standard, but also connected particles in which the primary particles are tightly connected and cannot be easily disintegrated, and which have a particle diameter equal to or larger than the standard particle diameter.
[0006] In order to obtain nickel powder that does not contain particles larger than these standard particle sizes, classification processing using expensive classification equipment is essential. In classification processing, it is possible to remove coarse particles larger than the classification point of an arbitrary value of about 0.6 μm to 2 μm, but there is also a problem that some of the particles smaller than the classification point are removed at the same time, resulting in a significant decrease in the actual product yield.
[0007] For example, Patent Document 1 discloses a method for producing nickel powder, which is characterized in that the produced nickel particles are disintegrated using a jet mill equipped with a high-speed classification rotor, and coarse particles are removed before re-agglomeration.
[0008] Furthermore, as a method for obtaining a conductive paste that does not contain coarse particles, there is a conventional method in which the conductive paste is filtered through a filter to remove the coarse particles.
[0009] For example, Patent Document 2 discloses a method for removing coarse metal particles having a predetermined particle size or more by filtering a slurry containing metal particles as the main solid content (hereinafter referred to as "metal particle slurry") through a filter, the method comprising the steps of: providing a circulation line for extracting the metal particle slurry from a slurry chamber functioning as a filter front chamber to which the metal particle slurry to be passed through the filter is supplied, circulating the metal particle slurry through a predetermined path, and returning the slurry chamber again; filtering the metal particle slurry in the slurry chamber through a filter having a predetermined mesh size while circulating the metal particle slurry through the circulation line, thereby removing the coarse metal particles. Patent Document 2 also discloses a method for recovering the coarse metal particles by using a low-boiling-point dispersant as a dispersant, and distilling off the dispersant and solvent from the metal particle slurry after separation of the coarse metal particles. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2003-089806 A [Patent Document 2] JP 2002-177743 A Summary of the Invention [Problem to be solved by the invention]
[0011] However, even if the inorganic particles are classified in advance to remove coarse particles as in Patent Document 1, the inorganic particles may re-aggregate to form coarse particles during the subsequent storage and manufacturing steps.
[0012] In addition, in the process of filtering the metal particle slurry while circulating it as described in Patent Document 2, the dispersion of the metal particle slurry is not sufficiently maintained, and clogging occurs due to the agglomeration of metal particles, which may result in inability to accurately remove coarse particles. In addition, an additional process of removing the low boiling point dispersant and the solvent is required after removing the coarse particles. In particular, in the case of a high-viscosity conductive paste used in a multilayer ceramic capacitor, even if a filter with high filtering accuracy is used to remove the coarse particles, clogging occurs, making it difficult to sufficiently reduce the number of coarse particles.
[0013] Taking these circumstances into consideration, the inventors conducted intensive research and discovered that in the manufacturing process of a conductive paste containing inorganic particles, by controlling the viscosity of an inorganic particle slurry having a specific composition within a specific range and removing coarse particles using a filter with high filtration accuracy, it is possible to greatly reduce the number of particles (coarse particles) having a standard particle size of about twice the average particle size, even in a highly viscous conductive paste, and thus completed the present invention.
[0014] An object of the present invention is to provide a conductive paste which has excellent dispersibility and high viscosity, yet contains a significantly reduced number of coarse particles. [Means for solving the problem]
[0015] In a first aspect of the present invention, there is provided a conductive paste comprising inorganic particles, a binder resin, a dispersant, and an organic solvent, wherein the inorganic particles comprise conductive powder having a number average particle size of 0.05 μm or more and 0.3 μm or less, in an amount of 30 mass % or more and 70 mass % or less relative to the entire conductive paste, the binder resin comprises a cellulose-based resin, the dispersant comprises an acid-based dispersant, the conductive paste has a viscosity of more than 20 Pa·S at a shear rate of 4 s-1, and the proportion of conductive powder particles having a particle size exceeding twice the number average particle size of the conductive powder particles in the conductive paste is 50 ppm or less relative to the total number of conductive powder particles.
[0016] In a second aspect of the present invention, there is provided a method for producing the above-mentioned conductive paste, comprising: a first step of mixing inorganic particles, a binder resin, a dispersant, and an organic solvent to obtain an inorganic particle slurry; a second step of filtering the inorganic particle slurry through a filter having a filtration accuracy of 1.0 μm or less; and a third step of mixing the filtered inorganic particle slurry with a binder resin and an organic solvent.
[0017] In a third aspect of the present invention, there is provided an electronic component formed using the above-mentioned conductive paste.
[0018] In a fourth aspect of the present invention, there is provided a multilayer ceramic capacitor having at least a laminate in which dielectric layers and internal electrode layers are laminated, the internal electrode layers being formed using the above-mentioned conductive paste. Effect of the Invention
[0019] The conductive paste of the present invention has excellent dispersibility and high viscosity, but the number of coarse particles is significantly reduced. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a diagram showing an example of a primary particle (single particle) of a conductive powder (inorganic particle). [Diagram 2] FIG. 2 is a diagram showing an example of connected particles of conductive powder (inorganic particles). [Diagram 3] FIG. 3 is a diagram illustrating an example of a method for producing a conductive paste according to an embodiment. [Figure 4] FIG. 4 is a perspective view and a cross-sectional view showing the multilayer ceramic capacitor according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] [Conductive paste] (Paste Viscosity) The conductive paste in this embodiment contains inorganic particles (including conductive powder), a binder resin, a dispersant, and an organic solvent. -1 The viscosity at is more than 10 Pa·S, and may be, for example, more than 10 Pa·S and not more than 100 Pa·S, 15 Pa·S or more and not more than 50 Pa·S, or 20 Pa·S or more and not more than 40 Pa·S. When the viscosity of the conductive paste is in the above range, it can be suitably used, for example, as a paste for screen printing.
[0022] In the conductive paste having a relatively high viscosity as described above, when a filter with high filtering accuracy is used to remove coarse particles having a particle size of a certain size or more, clogging occurs, making it difficult to sufficiently reduce the number of coarse particles. In the conductive paste of the present embodiment, although the paste has a relatively high viscosity, the number of coarse particles in the conductive paste can be significantly reduced by using a method for producing the conductive paste, which will be described later.
[0023] FIG. 1 shows an example of a primary particle (single) of the conductive powder contained in the conductive paste, and FIG. 2 shows an example of a connected particle of the conductive powder contained in the conductive paste. In this specification, the term "coarse particles" refers not only to particles whose primary particle (single) particle size is larger than a reference particle size (for example, twice the number average particle size of the conductive powder), but also to particles whose connected particles (see FIG. 2) formed by connecting primary particles with smaller particle sizes are larger than a reference particle size. The particle size of the conductive powder refers to the major axis (the major axis dimension of a circumscribed rectangular parallelepiped) determined from a scanning electron microscope (SEM) image. Each component contained in this embodiment will be described in detail below.
[0024] (Inorganic particles) The inorganic particles include a conductive powder. The inorganic particles may or may not include a ceramic powder. Each component of the inorganic particles will be described in detail below.
[0025] (a) Conductive powder The conductive powder is not particularly limited, and metal powder can be used, for example, powder of one or more selected from Ni, Pd, Pt, Au, Ag, Cu, and alloys thereof. Among these, from the viewpoints of conductivity, corrosion resistance, and cost, powder of Ni or its alloy (hereinafter, sometimes referred to as "nickel powder") is preferable. As the Ni alloy, for example, an alloy of Ni and at least one element selected from the group consisting of Mn, Cr, Co, Al, Fe, Cu, Zn, Ag, Au, Pt, and Pd can be used. The content of Ni in the Ni alloy is, for example, 50 mass% or more, preferably 80 mass% or more. In addition, the nickel powder may contain about several hundred ppm of element S in order to suppress sudden gas generation due to partial thermal decomposition of the binder resin during the binder removal process.
[0026] In addition, when nickel powder is used as the conductive powder, the manufacturing method is not particularly limited, and it can be manufactured using a conventionally known wet method or dry method. For example, the nickel powder may be nickel powder manufactured by a so-called dry method such as a CVD method, an evaporation quenching method, or a hydrogen reduction method using nickel salt or nickel hydroxide, or may be nickel powder manufactured by a so-called wet method such as a wet reduction method using a reducing agent such as hydrazine for a nickel salt solution. Among them, it is preferable to use nickel powder manufactured by a so-called wet method such as a wet reduction method. For example, it is known that the wet reduction method can manufacture nickel powder with a relatively narrow particle size distribution, but in the conventional manufacturing method of nickel powder, coarse particles are contained at a certain rate, and it is difficult to completely remove the coarse particles.
[0027] The number average particle size of the conductive powder is, for example, 0.05 μm or more and 0.3 μm or less, preferably 0.05 μm or more and 0.3 μm or less, and more preferably 0.1 μm or more and 0.2 μm or less. When the average particle size of the conductive powder is within the above range, it can be suitably used as a paste for internal electrodes of a thin-film multilayer ceramic capacitor (multilayer ceramic component). In the conductive paste of this embodiment, by using a method described later, even if the average particle size of the conductive powder is within the above range, the number of coarse particles is sufficiently reduced, and a dry film with high smoothness can be formed.
[0028] The average particle size is a value determined by observation with a scanning electron microscope (SEM), and is the average value (SEM average particle size, number average) obtained by measuring the particle size of each of multiple particles from an image observed with an SEM at 10,000 times magnification.
[0029] The specific surface area of the conductive powder is, for example, 2 m 2 / g or more 50m 2 / g or less, and 2.5m 2 / g or more 40m 2 / g or less, 2 / g or more 20m 2 When the specific surface area of the conductive powder is large, the surface activity is high, dispersibility is reduced, and the powder particles tend to aggregate with each other, and the liquid permeability through the filter may be reduced. 2 / g or more, or 5m 2 / g or more, the amount of coarse particles can be sufficiently reduced. The specific surface area of the conductive powder can be determined by the BET method using nitrogen gas adsorption.
[0030] The content of the conductive powder is preferably 30% by mass or more and less than 70% by mass, more preferably 40% by mass or more and 60% by mass or less, based on the entire conductive paste. When the content of the conductive powder is within the above range, the conductive paste has excellent conductivity and dispersibility. The content of the conductive powder may be more than 50% by mass.
[0031] (b) Ceramic powder The ceramic powder is not particularly limited, and for example, in the case of a paste for an internal electrode of a multilayer ceramic capacitor, a known ceramic powder is appropriately selected depending on the type of multilayer ceramic capacitor to be applied. As the ceramic powder, for example, a perovskite oxide containing Ba and Ti can be used, and preferably contains barium titanate (BaTiO3).
[0032] The ceramic powder may be a ceramic powder containing barium titanate as a main component and oxides as sub-components. Examples of oxides include oxides of Mn, Cr, Si, Ca, Ba, Mg, V, W, Ta, Nb, and one or more rare earth elements. The ceramic powder may be a perovskite-type oxide ferroelectric ceramic powder in which the Ba and Ti atoms of barium titanate (BaTiO3) are replaced with other atoms, such as Sn, Pb, and Zr.
[0033] When used as a conductive paste for internal electrodes, the ceramic powder may be powder of the same composition as the dielectric ceramic powder constituting the green sheet of the multilayer ceramic capacitor (electronic component). This suppresses the occurrence of cracks due to a mismatch in shrinkage at the interface between the dielectric layer and the internal electrode layer during the sintering process. In addition to the above, examples of such ceramic powder include oxides such as ZnO, ferrite, PZT, BaO, Al2O3, Bi2O3, R (rare earth element)2O3, TiO2, and Nd2O3. Note that one type of ceramic powder may be used, or two or more types may be used.
[0034] The number average particle size of the ceramic powder is, for example, 0.01 μm or more and 0.3 μm or less. The number average particle size of the ceramic powder may be smaller than the number average particle size of the conductive powder, for example, 1 / 2 or less of the average particle size of the conductive powder. When the number average particle size of the ceramic powder is in the above range, it is possible to form a sufficiently fine, thin and uniform internal electrode when used as an internal electrode paste. The number average particle size is a value determined by observation with a scanning electron microscope (SEM), and is the average value (SEM average particle size, number average) obtained by measuring the particle size of each of a plurality of particles from an image observed with an SEM at a magnification of 50,000 times.
[0035] The specific surface area of ceramic powder is, for example, 5 m 2 / g or more 100m 2 / g or less, 2 / g or more 80m 2 / g or less, 2 / g or more 60m 2 The specific surface area of the conductive powder can be determined by the BET method using nitrogen gas adsorption.
[0036] The content of the ceramic powder is preferably 1% by mass or more and 20% by mass or less based on the entire conductive paste, and the upper limit of the ceramic powder content may be 15% by mass or less, 10% by mass or less, or 6% by mass or less.
[0037] The content of the ceramic powder is, for example, 2 parts by mass or more and 40 parts by mass or less, relative to 100 parts by mass of the conductive powder, and may be 30 parts by mass or less, 20 parts by mass or less, or 12 parts by mass or less.
[0038] (binder resin) The binder resin preferably contains a cellulose-based resin. The cellulose-based resin is not particularly limited, and a known cellulose-based resin (cellulose derivative) used as a binder resin can be used. Examples of the cellulose-based resin include ethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, propyl cellulose, and acetyl cellulose. The cellulose-based resin may be used alone or in combination of two or more kinds.
[0039] The cellulose-based resin preferably contains ethyl cellulose resin. When the cellulose-based resin contains ethyl cellulose resin, the solubility in organic solvents and the combustion decomposition property are excellent. In addition, in the manufacturing process of the conductive paste, when the inorganic particle slurry contains ethyl cellulose resin, the dispersibility of the inorganic particle slurry and the liquid permeability through the filter are improved, and the number of coarse particles can be accurately reduced.
[0040] The weight average molecular weight (Mw) of the cellulose resin may be 10,000 or more and 300,000 or less, 30,000 or more and 250,000 or less, or 50,000 or more and 200,000 or less. The hydroxyl value of the cellulose resin is not particularly limited, but is preferably 0.1 mgKOH / g or more and 15 mgKOH / g or less, more preferably 0.5 mgKOH / g or more and 7 mgKOH / g or less, and even more preferably 1.5 mgKOH / g or more and 3 mgKOH / g or less. The cellulose resin may be used alone or in combination of two or more kinds.
[0041] The content of the cellulose resin may be 0.1% by mass or more and 3.0% by mass or less, 0.5% by mass or more and 2% by mass or less, or 1.0% by mass or more and 2% by mass or less. The higher the content of the cellulose resin within the above range, the more improved the liquid permeability of the inorganic particle slurry.
[0042] The binder resin may also contain an acetal resin. The acetal resin preferably contains a butyral resin, and more preferably contains polyvinyl butyral (PVB). When the conductive paste contains an acetal resin, the adhesive strength with the green sheet can be further improved. In addition, in the manufacturing process of the conductive paste, the inorganic particle slurry contains an acetal resin, so that the dispersibility of the inorganic particle slurry and the liquid permeability through the filter are improved, and the number of coarse particles can be accurately reduced.
[0043] The weight average molecular weight (Mw) of the acetal resin may be from 30,000 to 300,000, from 50,000 to 200,000, or from 100,000 to 150,000. The glass transition temperature Tg of the acetal resin may be from 50° C. to 90° C., or from 60° C. to 80° C. The acetal resin may be used alone or in combination of two or more.
[0044] The content of the acetal resin may be 0.5% by mass or more and 3% by mass or less, 0.5% by mass or more and 2% by mass or less, or 1% by mass or more and 2% by mass or less. The higher the content of the acetal resin within the above range, the more improved the liquid permeability of the inorganic particle slurry.
[0045] In addition, resins other than the cellulose-based resin and the acetal-based resin may be contained as binder resins. The binder resin other than the above is not particularly limited, and known resins can be used, such as acrylic resins.
[0046] When the binder resin contains a cellulose-based resin and an acetal-based resin, the binder resin may contain 20% by mass or more, 40% by mass or more, or 55% by mass or more of the cellulose-based resin relative to the total content (100% by mass) of the cellulose-based resin and the acetal-based resin. When the resin content is within the above range, the dispersibility of the inorganic particles can be further improved, and the adhesive strength between the dry film and the green sheet (substrate) can be improved. The binder resin may contain a resin in which the cellulose-based resin and the acetal-based resin are bonded. In this case, it is preferable that the ratio of each constituent part of the cellulose-based resin and the acetal-based resin satisfies the above content and blending ratio.
[0047] The content of the binder resin is preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 5% by mass, based on the entire conductive paste. When the content of the binder resin is within the above range, the conductive paste has excellent conductivity and dispersibility.
[0048] The content of the binder resin is preferably 1 part by mass or more and 20 parts by mass or less, and more preferably 1 part by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the conductive powder.
[0049] (Organic solvent) The organic solvent is not particularly limited, and any known organic solvent capable of dissolving the binder resin can be used. The organic solvent can be appropriately selected from known organic solvents so that the viscosity of the inorganic particle slurry and the viscosity of the conductive paste are in the desired range. Examples of the organic solvent include terpene-based solvents, acetate-based solvents, ether-based solvents, ketone-based solvents, and hydrocarbon-based solvents.
[0050] Examples of the terpene solvent include terpineol, dihydroterpineol, and dihydroterpinyl acetate.
[0051] Examples of acetate solvents include isobornyl acetate, isobornyl propionate, isobornyl butyrate, and isobornyl isobutyrate; glycol ether acetates such as ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, dipropylene glycol methyl ether acetate, 3-methoxy-3-methylbutyl acetate, and 1-methoxypropyl-2-acetate; glycol diacetates such as propylene glycol diacetate, 1,4-butanediol diacetate, 1,3-butylene glycol diacetate, and 1,6-hexanediol diacetate; and cyclohexanol acetate.
[0052] Examples of the ether solvent include propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether; ethylene glycol ethers such as diethylene glycol mono-2-ethylhexyl ether, ethylene glycol mono-2-ethylhexyl ether, diethylene glycol monohexyl ether, and ethylene glycol monohexyl ether; dipropylene glycol methyl-n-propyl ether, dipropylene glycol methyl-n-butyl ether, and dipropylene glycol dimethyl ether.
[0053] Examples of the ketone solvent include methyl isobutyl ketone, diisobutyl ketone, etc. When a ketone solvent is contained, it is possible to adjust the viscosity without impairing the dispersibility, and it is also possible to improve the drying property.
[0054] Examples of the hydrocarbon solvent include solvents containing tridecane, nonane, cyclohexane, etc., mineral spirits, naphthenic solvents, etc., and among these, mineral spirits is preferred.
[0055] The organic solvent preferably contains at least one selected from the group consisting of terpineol, dihydroterpineol, dihydroterpinyl acetate, propylene glycol monobutyl ether, and diethylene glycol monobutyl ether acetate. By containing these organic solvents, the compatibility with the binder resin is excellent and the dispersibility of the filler is excellent.
[0056] The organic solvent may be one type or two or more types. For example, when two or more types of organic solvents are included, the organic solvent may include at least one selected from the group consisting of terpineol, dihydroterpineol, dihydroterpinyl acetate, propylene glycol monobutyl ether, and diethylene glycol monobutyl ether acetate, and a hydrocarbon-based solvent, or may include dihydroterpineol and a hydrocarbon-based solvent. In addition to these organic solvents, the organic solvent may include at least one selected from methyl isobutyl ketone and diisobutyl ketone.
[0057] The content of the organic solvent (total) is preferably 20% by mass to 60% by mass, more preferably 25% by mass to 50% by mass, based on the total amount of the conductive paste. When the content of the organic solvent is within the above range, the conductive paste has excellent conductivity and dispersibility.
[0058] The content of the organic solvent is preferably 40 parts by mass or more and 120 parts by mass or less, more preferably 50 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the conductive powder. When the content of the organic solvent is within the above range, the conductive powder has excellent conductivity and dispersibility.
[0059] The content of the hydrocarbon solvent may be from 10% by mass to 50% by mass, or from 20% by mass to 40% by mass, based on the total amount of the organic solvents.
[0060] (Dispersant) The conductive paste preferably contains a dispersant, more preferably an acid-based dispersant. By containing the acid-based dispersant, the dispersibility of the inorganic particles can be improved, and the liquid permeability of the inorganic particle slurry can be improved. In addition, by suppressing re-aggregation of the inorganic particles, the number of coarse particles in the conductive paste can be reduced.
[0061] The acid dispersant may include a carboxylic acid dispersant such as a higher fatty acid, a polycarboxylic acid dispersant, a phosphoric acid dispersant, an acid dispersant having an acidic group such as a polymer surfactant, and the like, and it is preferable to include at least one of a polycarboxylic acid dispersant and a phosphoric acid dispersant. The polycarboxylic acid dispersant may be a polycarboxylic acid having a graft chain, or a polycarboxylic acid having a graft chain polyoxyalkylene. The phosphoric acid dispersant may be a phosphoric acid polyester. The dispersant may be used alone or in combination of two or more kinds.
[0062] The acid dispersant is preferably contained in an amount of 0.01% by mass or more and less than 1.0% by mass with respect to the entire conductive paste, and may be contained in an amount of 0.05% by mass or more and 0.5% by mass or less.
[0063] The content of the acid-based dispersant is determined based on, for example, the specific surface area (m 2 / g) is 0.02mgKOH / m 2 More than 0.30mgKOH / m 2 Less than 0.05 mgKOH / m 2 More than 0.25mgKOH / m 2 Less than or equal to 0.08 mgKOH / m 2 More than 0.20mgKOH / m 2 It can be adjusted to the following range:
[0064] In addition, when the acid-based dispersant contains a polycarboxylic acid-based dispersant, the content of the polycarboxylic acid-based dispersant is, for example, based on the specific surface area (m2 / g) is 0.01mgKOH / m 2 More than 0.10mgKOH / m 2 Less than or equal to 0.02 mgKOH / m 2 More than 0.07mgKOH / m 2 Less than or equal to 0.02 mgKOH / m 2 More than 0.06mgKOH / m 2 It can be adjusted to the following range:
[0065] In addition, when the acid-based dispersant contains a phosphoric acid-based dispersant, the content of the phosphoric acid-based dispersant is, for example, based on the specific surface area (m 2 / g) is 0.01mgKOH / m 2 More than 0.20mgKOH / m 2 Less than 0.05 mgKOH / m 2 More than 0.17mgKOH / m 2 Less than or equal to 0.08 mgKOH / m 2 More than 0.16mgKOH / m 2 It can be adjusted to the following range:
[0066] By adjusting the content of the acid dispersant within the above range, the dispersibility of the inorganic particles can be improved, the liquid permeability of the inorganic particle slurry can be further improved, and the re-aggregation of the inorganic particles can be further suppressed. The acid value (mgKOH / g) can be determined, for example, by potentiometric titration in accordance with JIS K0070.
[0067] The acid value of the dispersant relative to the specific surface area of the entire inorganic particles can be calculated by the following method. That is, the acid value of the dispersant (e.g., X mgKOH / g) is multiplied by the content of the dispersant in the entire conductive paste (e.g., x mass%) to obtain a value (X×x). The specific surface area (e.g., Am m 2 / g, B m 2The value is obtained by multiplying the content (a mass % or b mass %) of each of the conductive pastes in the entire conductive paste (for example, a mass %, b mass %) and dividing the result by the sum (A×a+B×b) (i.e., X×y / (A×a+B×b)).
[0068] The conductive paste may also contain a dispersant other than the acid dispersant, for example, a base dispersant, a nonionic dispersant, an amphoteric dispersant, or the like.
[0069] The dispersant is contained in an amount of, for example, 0.01% by mass or more and 3% by mass or less based on the entire conductive paste. The range including the upper limit of the dispersant content may be 2% by mass or less, 1% by mass or less, or 0.6% by mass or less.
[0070] (Other additives) The conductive paste of the present embodiment may contain other additives in addition to the above components, as necessary. As the other additives, for example, conventionally known additives such as an antifoaming agent, a plasticizer, and a thickener can be used.
[0071] (Characteristics of conductive paste) (1) Number of coarse particles In the conductive paste of this embodiment, the proportion of conductive powder whose particle diameter observed by a scanning electron microscope is more than twice the number average particle diameter of the conductive powder (hereinafter, simply referred to as "coarse particles") is, for example, 50 ppm or less relative to the total number of conductive powder, and the coarse particles (including single primary particles and connected particles) contained in the conductive paste can be significantly reduced. In addition, the number of coarse particles may be 40 ppm or less, 20 ppm or less, 10 ppm or less, 5 ppm or less, or 0 ppm.
[0072] The proportion of the number of coarse particles can be calculated, for example, by the following method.
[0073] First, 5 mg of the conductive paste was diluted with an organic solvent (e.g., 4000 times diluted with dihydroterpineol) to prepare a sample liquid, and the sample liquid was filtered through a filter having a pore size of less than twice the number average particle size of the conductive powder (e.g., a 0.4 μm filter when the number average particle size of the conductive powder is 0.2 μm) to remove some fine particles. Then, using a scanning electron microscope (SEM), the conductive particles on the filter were observed at a magnification of 5000 times, and 10 fields of view were photographed. From the photographed images, the coarse particles (primary particles and connected particles) were counted, and the number ratio of the coarse particles was calculated using the following (Equation 1).
[0074] Ratio of coarse particles to the total number of coarse particles counted / number of conductive powder particles corresponding to the observed field of view (Equation 1)
[0075] The number of conductive powder particles corresponding to the observed field area means the number of conductive powder particles (total) used to count the coarse particles, and is calculated by the following (Equation 2).
[0076] Number of conductive powder particles corresponding to the observed field area = (number of conductive powder particles used in sample preparation) × (observed field area) / (total area of filtration filter) (Equation 2)
[0077] The number of conductive particles used in sample preparation is determined by the weight of the conductive paste used in sample preparation (a, unit: g), the concentration (weight percent concentration) of the conductive powder in the conductive paste (b, unit: wt%), and the true density of the conductive powder (c, unit: g / cm 3 ) and the number average particle size of the conductive powder (d, unit: cm), it is calculated from the following (Equation 3).
[0078] Number of conductive particles used in sample preparation =(a×b / c)÷(4 / 3π(1 / 2d) 3 )...(Formula 3)
[0079] In addition, when the conductive powder is nickel powder, the true density is 8.9 g / cm 3In addition, the organic solvent used in sample preparation may be the main solvent (the solvent with the highest content) of the conductive paste.
[0080] The amount of conductive paste filtered by the area of the observed image (area of the observed field of view) may be, for example, 0.02 μg or more of conductive paste. The amount of conductive paste to be evaluated may be changed depending on the amount of conductive paste, the area of the filter, and the number of fields of view. However, if the amount is small, the number of coarse particles detected may decrease and the variation may increase, so it is preferable to use the above amount of conductive paste or more. In addition, if the area of the filter is small and the entire field of view can be observed, the number of coarse particles in the conductive paste used for evaluation can be determined more accurately.
[0081] Alternatively, the number of coarse particles may be directly measured by applying and drying the conductive paste, observing it with an SEM, and counting the number of coarse particles. For example, ten SEM images at a magnification of 5000 times may be obtained, and the number may be counted using image analysis software. In this case, the number of coarse particles counted may be divided by the total number of particles in the observed conductive powder to calculate the proportion of the number of coarse particles.
[0082] In addition, in the conductive paste of this embodiment, the percentage of conductive powder particles having a particle diameter of more than 0.4 μm as observed by a scanning electron microscope may be, for example, 40 ppm or less, 20 ppm or less, 10 ppm or less, 5 ppm or less, or 0 ppm.
[0083] (2) Surface roughness of dried film The surface roughness (arithmetic mean height Sa) of the dry film formed by printing the conductive paste is, for example, 0.1 μm or less, or may be 0.08 μm or less, 0.06 μm or less, or 0.05 μm or less. The surface roughness of the conductive paste can be measured, for example, by the method described in the Examples (a method of measuring the arithmetic mean height Sa based on the ISO 25178 standard using an OLS5000 manufactured by Evident Co., Ltd.).
[0084] The conductive paste according to the present embodiment can be suitably used in electronic components such as multilayer ceramic capacitors. The multilayer ceramic capacitor has, for example, dielectric layers formed using dielectric green sheets and internal electrode layers formed using the conductive paste.
[0085] For example, the thickness of the internal electrode layer formed using the conductive paste of this embodiment may be, for example, 1.5 μm or less, 1 μm or less, or 0.7 μm or less. The conductive paste of this embodiment has good dispersibility and a small number of coarse particles, so that a thin internal electrode layer can be manufactured with high reliability.
[0086] [Method of manufacturing conductive paste] The method for producing the conductive paste according to the present embodiment will be described below. Fig. 3 is a diagram showing an example of the method for producing the conductive paste. As shown in Fig. 3, the method for producing the conductive paste according to the present embodiment includes the following steps (1) to (3).
[0087] (1) A first step (S1) of mixing inorganic particles, a binder resin, a dispersant, and an organic solvent to obtain an inorganic particle slurry. (2) A second step (S2) of filtering the inorganic particle slurry through a filter having a filtering accuracy of 1.0 μm or less. (3) A third step (S3) of kneading the inorganic particle slurry after filtration with a binder resin and an organic solvent.
[0088] 3 shows an example of a method for producing a conductive paste, but the method is not limited to these methods. The conductive paste of this embodiment is preferably used for forming an internal electrode of a multilayer ceramic capacitor. Each step will be described in detail below.
[0089] (1st step: S1) In the first step (S1), inorganic particles, a binder resin, a dispersant, and an organic solvent are mixed to obtain an inorganic particle slurry (step S1). The inorganic particle slurry contains, for example, coarse particles (e.g., inorganic particles having a particle diameter of more than 0.4 μm). The coarse particles are removed from the inorganic particle slurry in the second step (S2) described later.
[0090] The inorganic particle slurry obtained in the first step (S1) is subjected to a shear rate of 4 s at room temperature (25 °C). -1 The viscosity of the inorganic particle slurry is 20 Pa·s or less at a shear rate of 4 s -1 The viscosity of the inorganic particle slurry may be, for example, 10 Pa·s or less, or 5 Pa·s or less. -1 The lower limit of the viscosity is not particularly limited, and the lower the viscosity, the easier it is to improve the liquid permeability. -1 The lower limit of the viscosity is, for example, 1 Pa·s or more, or even if it is 2 Pa·s or more, the number of coarse particles can be sufficiently reduced.
[0091] The inorganic particle slurry obtained in the first step (S1) was subjected to a shear rate of 40 s at room temperature (25°C). -1 The viscosity at a shear rate of the inorganic particle slurry is preferably 5 Pa·s or less, and more preferably 1 Pa·s or less. -1 The lower limit of the viscosity is not particularly limited, and the lower the viscosity, the easier it is to improve the liquid permeability. -1 The lower limit of the viscosity is, for example, 0.3 Pa·s or more, or even if it is 0.4 Pa·s or more, the number of coarse particles can be sufficiently reduced.
[0092] The viscosity of the inorganic particle slurry can be controlled within the above range by adjusting the type and content of each component contained in the inorganic particle slurry. In the manufacturing method of this embodiment, the composition and viscosity characteristics of the inorganic particle slurry obtained in the first step (S1) are adjusted to improve the dispersibility of the inorganic particles while suppressing re-aggregation of the inorganic particles, thereby enabling the use of a filter with high filtration accuracy in the second step (S2).
[0093] The inorganic particles contained in the inorganic particle slurry may include conductive powder, or may include both conductive powder and ceramic powder. The inorganic particles include single primary particles and connected particles formed by connecting primary particles. The conductive powder used as a raw material may also include coarse particles, and may include, for example, more than 50 ppm, 70 ppm or more, or 90 ppm or more of particles having a particle diameter more than twice the number average particle diameter of the conductive powder. In this specification, the coarse particles include not only particles whose particle diameter of the primary particles (single particles) is larger than the reference particle diameter, but also particles whose particle diameter of the connected particles (see FIG. 2) formed by connecting primary particles having small particle diameters is larger than the reference particle diameter.
[0094] The inorganic particle slurry contains a binder resin. The binder resin contained in the inorganic particle slurry preferably contains a cellulose-based resin, and more preferably contains both a cellulose-based resin and an acetal-based resin. The cellulose-based resin may be contained in an amount of, for example, 0.1% by mass to 3.0% by mass, 0.2% by mass to 2.0% by mass, or 0.2% by mass to 1.5% by mass, based on the entire inorganic particle slurry. The acetal-based resin may be contained in an amount of, for example, 0.5% by mass to 3% by mass, or 0.5% by mass to 2% by mass, based on the entire inorganic particle slurry.
[0095] The content of the cellulose resin in the inorganic particle slurry is 0.5 g / m relative to the specific surface area of the inorganic particles. 2 More than 5g / m 2 It is preferable that the content is 0.5 g / m or less. 2 More than 3g / m 2 It may be less than 1 g / m 2 More than 3g / m 2 When the cellulose-based resin is contained in the above range, the dispersibility of the inorganic particles is further improved. In addition, the content of the cellulose-based resin contained in the inorganic particle slurry is 0.5 g / m or less relative to the specific surface area of the conductive powder. 2 More than 5g / m 2It may be less than 0.5 g / m 2 More than 3g / m 2 It may be less than 1 g / m 2 More than 3g / m 2 It may be the following.
[0096] The components used for mixing may be the same as those contained in the conductive paste described above. All components, except for a part of the binder resin and a part of the organic solvent, may be dispersed (mixed) to obtain an inorganic particle slurry among the components contained in the finally obtained conductive paste. The binder resin may be dispersed (mixed) using the entire amount of the acetal resin contained in the finally obtained conductive paste to obtain an inorganic particle slurry.
[0097] The mixing method is not particularly limited, and a known method can be used. Examples of the device used for mixing include a high-pressure homogenizer, a mixer, a suction dispersion stirrer, a bead mill, a ball mill, and a three-roll mill. For example, a high-pressure homogenizer may be used. The high-pressure homogenizer utilizes a fine orifice to generate a high-speed jet flow. The orifice diameter of the high-pressure homogenizer is not particularly limited, but may be, for example, 0.05 to 0.2 mm. In addition, the conditions in the high-pressure homogenizer (e.g., the number of dispersion passes) can be appropriately selected depending on the required particle diameter, particle size distribution, and the like. The number of dispersion passes may be performed with a device configuration that circulates the paste. In addition, when the inorganic particles form aggregates or the like and are difficult to disperse, a three-roll mill may be used for dispersion treatment. In addition, in the first step (S1), all the components may be mixed at once to obtain an inorganic particle slurry, or a part of the components may be mixed in multiple times to obtain an inorganic particle slurry. In addition, one or more devices may be used for mixing. For example, the components other than a portion of the organic solvent may be dispersed using a dispersing device (e.g., a three-roll mill), and then the organic solvent may be further added and stirred to obtain an inorganic particle slurry having a viscosity in the above-mentioned range.
[0098] (2nd process: S2) In the second step (S2), the inorganic particle slurry is filtered through a filter having a filtering accuracy of 1.0 μm or less. By using a filter with a relatively high filtering accuracy, coarse particles that are larger than the standard particle size can be removed.
[0099] The filter used in the second step may have a filtration accuracy of 1.0 μm or less, 0.8 μm or less, 0.6 μm or less, or 0.4 μm or less. The filtration accuracy can be appropriately selected depending on the particle size of the target inorganic particles. The lower limit of the filtration accuracy of the filter is, for example, 0.1 μm or more. The filtration accuracy generally indicates the size of particles that can be removed by passing through a filter, and may be expressed as a particle size that can capture 99% or more of particles when the fluid is water and fine dust is filtered through a 10-inch cartridge at a specified flow rate. In addition, due to its structure, particles smaller than the value indicated by the filtration accuracy can also be captured.
[0100] In the second step, the amount of liquid passing through the filter may be 50 g / min or more, 100 g / min or more, or 300 g / min or more when the filter is used with a total built-in filter length of 25 mm and filtered at a differential pressure of 0.39 MPa. When the amount of liquid passing through the filter is within the above range, the conductive paste can be produced with high productivity.
[0101] (3rd step: S3) In the third step (S3), the inorganic particle slurry after filtration is mixed with a binder resin and an organic solvent. After mixing, the conductive paste described above can be obtained with a reduced number of coarse particles. In this step, components other than the binder resin and the organic solvent (e.g., ceramic powder, other additives, etc.) may be added.
[0102] The binder resin added in the third step (S3) may contain a cellulose-based resin, may contain a cellulose-based resin and an acetal-based resin, or may be a cellulose-based resin (eg, ethyl cellulose) alone.
[0103] The organic solvent added in the third step (S3) is not particularly limited, and may be the same type as the organic solvent added in the first step (S1), and may, for example, contain a terpene-based solvent or may be a terpene-based solvent alone.
[0104] The mixing method is not particularly limited, and a conventionally known method can be used. For example, the mixing can be performed by stirring and kneading the above-mentioned components using a three-roll mill, a ball mill, a mixer, or the like.
[0105] [Multilayer ceramic capacitors] Hereinafter, embodiments of the multilayer ceramic capacitor of the present invention will be described with reference to the drawings. In the drawings, the drawings may be expressed diagrammatically or at a different scale as appropriate. The positions and directions of the members will be described with reference to an XYZ orthogonal coordinate system as shown in FIG. 4 as appropriate. In this XYZ orthogonal coordinate system, the X and Y directions are horizontal directions, and the Z direction is vertical (up-down direction).
[0106] 4A and 4B are diagrams showing the multilayer ceramic capacitor 1. The multilayer ceramic capacitor 1 includes an external electrode 20 and a ceramic laminate 10 in which dielectric layers 12 and internal electrode layers 11 are alternately laminated.
[0107] A method for manufacturing a multilayer ceramic capacitor using the conductive paste is described below. First, the conductive paste is printed on a ceramic green sheet and dried to form a dry film. A plurality of ceramic green sheets having this dry film on the upper surface are laminated by pressure bonding to obtain a laminate, and the laminate is then fired and integrated to produce a ceramic laminate 10 in which internal electrode layers 11 and dielectric layers 12 are alternately laminated. Then, a pair of external electrodes 20 is formed on both ends of the ceramic laminate 10 to manufacture a multilayer ceramic capacitor 1. A more detailed description is given below.
[0108] First, a green sheet, which is an unfired ceramic sheet, is prepared. For example, the green sheet is prepared by adding a binder resin such as polyvinyl butyral and a solvent such as terpineol to a raw powder of a specific ceramic such as barium titanate, applying the paste for dielectric layer to a support film such as a PET film in a sheet form, and drying to remove the solvent. The thickness of the dielectric layer made of the green sheet is not particularly limited, but is preferably 0.05 μm or more and 3 μm or less from the viewpoint of the demand for miniaturization of the multilayer ceramic capacitor.
[0109] Next, the conductive paste is printed and applied to one side of the green sheet, and then dried to form a dry film on one side of the green sheet, to prepare a plurality of sheets. Note that, from the viewpoint of the requirement for thinning the internal electrode layer 11, it is preferable that the thickness of the dry film formed from the conductive paste is 1 μm or less after drying.
[0110] Next, the green sheet is peeled off from the support film, and the green sheet and the dry film formed on one side thereof are laminated so as to be alternately arranged, and then a laminate is obtained by a heat and pressure treatment. Note that a configuration may be adopted in which protective ceramic green sheets not coated with the conductive paste are further arranged on both sides of the laminate.
[0111] Next, the laminate is cut to a predetermined size to form green chips, and the green chips are subjected to a binder removal treatment and fired in a reducing atmosphere to produce a laminated ceramic fired body (ceramic laminate 10). The binder removal treatment is preferably performed in air or N2 gas. The temperature during the binder removal treatment is, for example, 200°C or higher and 400°C or lower. The temperature is preferably held for 0.5 hours or higher and 24 hours or lower during the binder removal treatment. The firing is performed in a reducing atmosphere to suppress oxidation of the metal used in the internal electrode layer, and the temperature during firing of the laminate is, for example, 1000°C or higher and 1350°C or lower, and the temperature is held for, for example, 0.5 hours or higher and 8 hours or lower.
[0112] By firing the green chip, the organic binder in the ceramic green sheet is completely removed, and the ceramic raw material powder is fired to form the ceramic dielectric layer 12. The organic vehicle in the dry film is also removed, and the nickel powder or the alloy powder mainly composed of nickel is sintered or melted and integrated to form the internal electrode layer 11, forming a multilayer ceramic sintered body in which a plurality of dielectric layers 12 and internal electrode layers 11 are alternately stacked. Note that, from the viewpoint of taking oxygen into the dielectric layer to increase reliability and suppressing reoxidation of the internal electrodes, the multilayer ceramic sintered body after firing may be subjected to an annealing treatment.
[0113] A pair of external electrodes 20 is then provided on the produced fired laminated ceramic body to manufacture the laminated ceramic capacitor 1. For example, the external electrode 20 includes an external electrode layer 21 and a plating layer 22. The external electrode layer 21 is electrically connected to the internal electrode layer 11. Note that, for example, copper, nickel, or an alloy thereof can be suitably used as the material for the external electrode 20. Note that the electronic component can also be an electronic component other than a laminated ceramic capacitor. EXAMPLES
[0114] The present invention will be described in detail below based on examples and comparative examples, but the present invention is not limited to these examples.
[0115] [Evaluation method] (viscosity measurement) The viscosity of the conductive paste was measured using a rheometer (Anton Paar Japan Co., Ltd.: Rheometer MCR302). The viscosity was measured using a cone plate with a cone angle of 1° and a diameter of 25 mm at a shear rate of 4 sec. -1 , shear rate 40sec -1 The values measured under the above conditions were used.
[0116] (Number of large particles) The number of coarse particles in the conductive paste was measured by the following method.
[0117] 5 mg of conductive paste was diluted with 20 g of dihydroterpineol and the solution was passed through a 0.4 μm membrane filter (filter area: 1075 mm 2 The coarse particles collected on the filter surface were observed using a SEM (JSM-IT100, manufactured by JEOL Ltd.) at a magnification of 5000x and 10 fields of view (total field area 0.0049 mm2). 2 ) and primary particles larger than 0.4 μm in particle size and connected particles formed by connecting primary particles were counted as coarse particles. The amount of paste used in the observed field of view was calculated from the amount of conductive paste used in filtration and the ratio of the observed field of view area to the total area of the filtration filter to obtain the number of conductive powder particles with particle sizes exceeding 0.4 μm per 0.023 μg.
[0118] (Number average particle size of conductive powder) The number-average particle size of the conductive powder in the conductive paste is the average value obtained by measuring the particle size of 100 primary particles of the conductive powder present within a certain range of an image observed by SEM. The average particle size of the conductive powder is expressed with one significant digit.
[0119] (Surface roughness of dry film) A sample was applied (GAP thickness = 10 μm) onto a glass substrate (2 inches) and dried in an air atmosphere at a maximum temperature of 120 to 150°C in a belt furnace to produce a dry film with a thickness of 1 to 3 μm. When the conductive paste has good dispersibility, the surface of the dry film is smooth. When the dispersibility is poor, aggregation occurs within the conductive paste, the surface of the dry film becomes rough, and the surface Therefore, the surface roughness Sa (arithmetic mean height) of the prepared dry film was measured using a laser microscope (OLS5000 manufactured by Evident Co., Ltd.) based on the standard ISO 25178. The smaller the value of the surface roughness Sa (arithmetic mean height), the smoother the surface of the dry film is.
[0120] [Materials used] (conductive powder) The conductive powder was nickel powder A (number average particle size 0.2 μm, specific surface area 4.2 m 2 / g), and nickel powder b (number average particle size 0.2 μm, specific surface area 5.4 m 2 / g) was used.
[0121] (ceramic powder) The ceramic powder was barium titanate (BaTiO3, number average particle size 0.06 μm, specific surface area 23.4 m 2 / g) was used.
[0122] (binder resin) As the binder resin, polyvinyl butyral resin (PVB) and ethyl cellulose resin (EC) were used.
[0123] (Dispersant) As the acid-based dispersant, a polycarboxylic acid having a polyoxyalkylene as a graft chain (acid-based A) and a phosphoric acid polyester (acid-based B), which is a phosphoric acid-based dispersant, were used.
[0124] (Organic solvent) The organic solvents used were dihydroterpineol (DHT) and mineral spirits (MSA).
[0125] [Example 1] Conductive powder (Ni powder), ceramic powder (BaTiO3), dispersants (acid type A and acid type B), binder resins (EC, PVB), and organic solvents (DHT, MA) were mixed in the amounts shown in the first step of Table 2 (total 100 mass%) and dispersed using a high-pressure homogenizer to obtain an inorganic particle slurry (first step: S1).
[0126] The obtained inorganic particle slurry was then filtered through a filter with a filtering accuracy of 0.6 μm to remove at least a part of the coarse particles (second step: S2).
[0127] Thereafter, the filtered inorganic particle slurry was mixed with a binder resin and an organic solvent in the amounts shown in the third step in Table 4, and mixed using a mixer to prepare a conductive paste (third step: S3).
[0128] The properties of the obtained conductive paste (viscosity, surface roughness, number of coarse particles) were measured. The compounding ratio of each component of the conductive paste and the results are shown in Table 1.
[0129] [Examples 2 to 8] In Examples 2 to 8, conductive pastes were prepared and evaluated in the same manner as in Example 1, except that the type and content of each material used in the first and third steps were changed as shown in Tables 2 and 4. The content of each material in the conductive paste and the evaluation results are shown in Table 1. Table 3 also shows the acid value of the dispersant and the weight of the binder resin relative to the specific surface area of the inorganic particles added in the first step.
[0130] [Comparative Examples 1 to 3] In Comparative Example 1, the components were mixed in the amounts shown in Table 1, and only the dispersion treatment (first step) was carried out using a three-roll mill to prepare a conductive paste, which was then evaluated (the second and third steps were not carried out).
[0131] In Comparative Example 2, in order to confirm the effect of the resin on the state of the inorganic particle slurry produced in the first step, the inorganic particle slurry was obtained by dispersing with a high-pressure homogenizer under the same conditions as in Example 3, except that the resin used was changed from ethyl cellulose to polyvinyl butyral. The obtained inorganic particle slurry had low dispersibility and was difficult to filter, so the second and subsequent steps were not carried out. For reference, the inorganic particle slurry, which is an intermediate material, was evaluated as a conductive paste.
[0132] In Comparative Example 3, in order to confirm the effect of the resin on the state of the inorganic particle slurry produced in the first step, an inorganic particle slurry was obtained by dispersing with a high-pressure homogenizer under the same conditions as in Example 1, except that the resin component was removed in the first step. The obtained inorganic particle slurry had low dispersibility and was difficult to filter, so the second and subsequent steps were not performed. The evaluation results of the examples and comparative examples are shown in Table 1.
[0133] [Table 1]
[0134] [Table 2]
[0135] [Table 3]
[0136] [Table 4]
[0137] (Evaluation Results) The conductive pastes of Examples 1 to 8 had a reduced number of coarse particles despite their relatively high viscosity, and the surface roughness of the dried films was also sufficiently small, demonstrating excellent dispersibility.
[0138] On the other hand, in the conductive pastes of Comparative Examples 1 to 3, the number of coarse particles exceeded 50 ppm because the second step (filtration) was not performed. In Comparative Example 1, the viscosity of the inorganic particle slurry (conductive paste) obtained after the first step was high, and filtration with a filter was not possible. In Comparative Example 2, the binder resin was not added in the first step, and therefore the dispersibility of the inorganic particles was poor, and filtration with a filter was not possible. In Comparative Example 3, the ethyl cellulose resin was not added in the first step, and therefore although the paste viscosity was low, the dispersibility of the inorganic particles was poor, and filtration with a filter was not possible. [Industrial Applicability]
[0139] When the conductive paste of the present invention is used to form an internal electrode of a multilayer ceramic capacitor, a highly reliable multilayer ceramic capacitor can be obtained with high productivity. Therefore, the conductive paste of the present invention can be suitably used for the internal electrodes of multilayer ceramic capacitors, which are chip components of electronic devices such as mobile phones and digital devices that are becoming increasingly smaller.
[0140] The technical scope of the present invention is not limited to the aspects described in the above-mentioned embodiments. One or more of the requirements described in the above-mentioned embodiments may be omitted. The requirements described in the above-mentioned embodiments may be combined as appropriate. In addition, to the extent permitted by law, the disclosures of all documents cited in the above-mentioned embodiments are incorporated by reference and are included as part of the description in this text. [Explanation of symbols]
[0141] 1. Multilayer ceramic capacitors 10 Ceramic laminate 11 Internal electrode layer 12 Dielectric layer 20 External electrode 21 External electrode layer 22 Plating layer
Claims
1. A conductive paste comprising inorganic particles, a binder resin, a dispersant, and an organic solvent, The inorganic particles contain conductive powder having a number average particle size of 0.05 μm or more and 0.3 μm or less in an amount of 30% by mass or more and 70% by mass or less based on the entire conductive paste, The binder resin includes a cellulose-based resin, The dispersant includes an acid-based dispersant, The conductive paste is subjected to a shear rate of 4 s -1 The viscosity at is more than 10 Pa·S, In the conductive paste, the proportion of conductive powder particles having a particle diameter exceeding twice the number average particle diameter of the conductive powder particles is 50 ppm or less relative to the total number of the conductive powder particles. Conductive paste.
2. The conductive paste according to claim 1 , wherein the conductive powder contains at least one metal powder selected from the group consisting of Ni, Pd, Pt, Au, Ag, Cu, and alloys thereof.
3. 3. The conductive paste according to claim 1, wherein the inorganic particles contain ceramic powder having a number average particle size of 0.01 μm or more and 0.3 μm or less in an amount of 1 mass % to 20 mass % based on the entire conductive paste.
4. The conductive paste of claim 3 , wherein the ceramic powder comprises barium titanate.
5. The conductive paste according to claim 1 , wherein the cellulose-based resin is contained in an amount of 0.1% by mass to 3.0% by mass based on the conductive paste.
6. The conductive paste according to claim 1 , wherein the binder resin contains an acetal-based resin in an amount of 0.5% by mass to 3.0% by mass based on the entire conductive paste.
7. The conductive paste according to claim 1 , wherein the acid dispersant is contained in an amount of 0.01% by mass or more and less than 1.0% by mass based on the entire conductive paste.
8. A first step of mixing inorganic particles, a binder resin, a dispersant, and an organic solvent to obtain an inorganic particle slurry; A second step of filtering the inorganic particle slurry through a filter having a filtering accuracy of 1.0 μm or less; and a third step of mixing the filtered inorganic particle slurry with a binder resin and an organic solvent. The method for producing the conductive paste according to claim 1 .
9. The method for producing a conductive paste according to claim 8 , wherein the binder resin in the inorganic particle slurry contains a cellulose-based resin.
10. The method for producing a conductive paste according to claim 8 or 9, wherein the binder resin in the inorganic particle slurry contains a cellulose-based resin and an acetal-based resin.
11. The inorganic particle slurry obtained in the first step is subjected to a shear rate of 4 s at room temperature (25° C.). -1 The method for producing a conductive paste according to claim 8 or 9, wherein the viscosity of the conductive paste is 20 Pa·S or less.
12. 3. The method for producing a conductive paste according to claim 1, which is for use in an internal electrode of a multilayer ceramic part.
13. An electronic component formed by using the conductive paste according to claim 1 or 2.
14. The laminate has at least a dielectric layer and an internal electrode layer stacked thereon, The internal electrode layer is formed using the conductive paste according to claim 1 or 2. Multilayer ceramic capacitor.
Citation Information
Patent Citations
Method and apparatus for removing coarse metallic particle
JP2002177743A
Method for manufacturing nickel powder
JP2003089806A